Adjuvant chemotherapy may contribute to an increased risk for metabolic syndrome in patients with breast cancer. (February 2016) - Bicakli, Derya Hopanci; Varol, Umut; Degirmenci, Mustafa; Tunali, Didem; Cakar, Burcu; Durusoy, Raika; Karaca, Burcak; Ali Sanli, Ulus; Uslu, Ruchan
Purpose: Cytotoxic treatment may cause weight gain and important alterations in the metabolic status of breast cancer (BC) patients. The aim of this study was to investigate the changes in metabolic and anthropometric parameters of patients with BC who received adjuvant chemotherapy. Methods: All consecutive women treated with adjuvant TAC (docetaxel 75 mg/m 2, doxorubicine 50 mg/m 2, cyclophosphamide 500 mg/m 2 ) chemotherapy for node-positive breast carcinoma at our Institution between 2008 and 2010 were included. Results: Among 104 patients, 84 of them were stage II and 20 of them were stage III. When we compared the measurements between 1 st and 6 th adjuvant chemotherapy, we observed statistically significant increases in weight and serum triglyceride levels, and decreases in high density lipoprotein, apolipoprotein A-1, transferrin, albumin and prealbumin levels. An elevation of follicle stimulating hormone, luteinizing hormone together with the decrease of estradiol was detected. Waist-to-hip ratio has also increased significantly. In subgroup analyses, we observed dramatic changes in body mass index in pre-menopausal women whereas no significant change was seen in the post-menopausal group. Conclusions: Adjuvant chemotherapy may contribute to an increased risk for metabolic syndrome in patients with BC and these changes are more profound in pre-menopausal patients.